Attention Deficits in Children With Combined Autism and ADHD: A CPT Study. (July 2016) - Lundervold, Astri J.; Stickert, Marte; Hysing, Mari; Sørensen, Lin; Gillberg, Christopher; Posserud, Maj-Britt
Objective: To investigate characteristics of attention in children with the combination of autism spectrum disorder (ASD) and ADHD.Method: Four groups of 8- to 10-year-old children were compared on the Conners' Continuous Performance Test–Second Edition (CCPT-II): (a) ASD + ADHD ( n = 11), (b) ASD only ( n = 9), (c) ADHD only ( n = 38), and (d) no diagnosis ( n = 134).Results: There was an overall effect of group on the Continuous Performance Test (CPT) index and measures of hit reaction time, accuracy, response style, variability, and consistency. The ASD + ADHD group, much like the ADHD only group, had a more risky response style, a higher variability, and a lower consistency than the ASD only group. The impact of intellectual function on CCPT-II performance was considerable in children within the ASD subgroups.Conclusion: The findings underscore the importance of including measures of attention and intellectual function when assessing children with the combination of ASD and ADHD.